Legal Protection for Biznet Customers for Data Leak from the Perspective of Law Number 27 of 2022 - Romadona Putri Pertiwi; Ratih Damayanti (Law Research Review Quarterly, 2026)
The incident of PT Biznet Networks' data leak in March 2024 which impacted more than 380,000 customer data became the starting point of this study. This study aims to analyze two main problems: (1) legal protection and Biznet's responsibility for the leakage of customers' personal data based on Law Number 27 of 2022 concerning Personal Data Protection; and (2) critical evaluation of the Personal Data Protection Law in the case of Biznet data leak. This study applies a normative legal approach, supported by a regulatory analysis and a conceptual perspective. The findings of the study reveal that Biznet customers are positioned as Personal Data Subjects who receive layered protection from the Personal Data Protection Law, Consumer Protection Law, and Civil Code. Preventive protection is realized through a series of obligations imposed on data controllers, while repressive protection is available through three cumulative channels: administrative, civil, and criminal. Biznet is juridically positioned as the Personal Data Controller who bears the burden of reverse proof and non-delegable liability. The effectiveness of this legal framework is still constrained by the lack of independent supervisory institutions as mandated.